Cardiomyocytes as effectors of nitric oxide signalling. - Seddon, M; Shah, A; Casadei, B (2007)
Nitric oxide (NO) generated constitutively within the heart has long been known to influence myocardial function; however, the precise nature of these effects has been controversial--at least in part--because of the experimental use of non-isoform-selective inhibitors of NO synthases (NOS) and unwarranted extrapolation from results obtained with NO donors. Recent studies using NOS-selective inhibitors and genetically modified models are beginning to redress the balance. It is well established that agonist-stimulated release of NO from eNOS in the coronary endothelium exerts paracrine effects on cardiomyocytes, predominantly affecting the timing of relaxation as well as myocardial oxygen consumption. A significant recent advance has been the finding that both eNOS and nNOS are constitutively expressed in distinct subcellular locations within cardiomyocytes. The relative autocrine role of these isoforms in the cardiomyocyte remains to be fully clarified but evidence suggests that the autocrine effects of nNOS may include the modulation of basal inotropy and relaxation, beta-adrenergic responsiveness, and the force-frequency relationship. Myocardial eNOS, on the other hand, may be involved in mediating the inotropic response to sustained stretch. These effects may change significantly in the diseased heart where the expression, activity and/or coupling of NOS isoforms to downstream effectors may be altered. In this article, we review the current understanding of this important but complex field, focussing particularly on contractile function and on recent advances in knowledge regarding the autocrine functions of nNOS-derived NO.